Emblems on Coins and Medals in Seventeenth-Century Sweden - Haidenthaller, Ylva ; 0009-0000-7489-4754 (Emblematica Essays in Word and Image, 2025)
This paper provides a comprehensive overview of how emblems were used on Swedish royal medals and commemorative coins during the seventeenth century, a period marked by the rise of the Swedish Empire. Focusing on numismatic objects that thematize royal succession and coronations, it focuses on how emblems were utilized across multiple monarchs, touching on the origin of the emblems and how the use of emblems changed during the century. Consequently, the article reveals insights into emblems and medals embodying symbolic power and political significance.
Keywords: emblems; numismatics; medals; coins; Sweden; royal imagery